Economics of Inhaled Oxygen Use as an Acute Therapy for Cluster Headache in the United States of America. Issue 9 (26th August 2017) - O'Brien, Megan; Ford, Janet H.; Aurora, Sheena K.; Govindan, Sriram; Tepper, Deborah E.; Tepper, Stewart J.
Abstract : Background: Cluster headache (CH) is a primary headache disorder associated with low levels of diagnosis and high unmet medical need. The pain attacks, associated anxiety, and fear in anticipation of the attacks are extremely debilitating to a patient with CH. For acute therapy, treatment guidelines recommend inhalation of high flow oxygen during the period of an attack. However, the use of oxygen for treatment of CH remains largely underutilized. Objectives: The objectives of the study, which covered each of the US states, were to map the current market landscape of medical grade oxygen for use in CH and to develop a cost simulator based on a patient's needs and geography. Methods: Desk research was undertaken to obtain price lists and product catalogs from wholesale and retail suppliers of medical grade oxygen across all US states. Base case scenarios for chronic and episodic forms of CH were assumed. A cost simulator was used to calculate the cost of oxygen use using inputs including the state in USA, tank size and price, exacerbations per year, duration of exacerbation, attacks per day, flow rate and duration of flow. Information was also collected to determine if healthcare insurers covered the costs of home oxygen use for CH. Results: Out of the 42 US states where pricing information of medical grade oxygen was available from suppliers, in 38 states the annual cost of high‐flow oxygen for a patient with episodic CH was estimated to be <1000. In 39 states, the annual cost of high‐flow oxygen for a patient with chronic CH was estimated to be <5000. Most of the home oxygen suppliers were familiar with CH and stocked the special non‐rebreather masks and regulators necessary for this condition. It was found that many of the private commercial healthcare insurance providers reimbursed the cost of oxygen use for CH. However, the US Centers for Medicare and Medicaid Services (CMS) maintains there is insufficient evidence for coverage and continues to deny coverage for US Medicare and Medicaid patients. Conclusions: Results from our study showed that the current costs for oxygen use as an acute therapy in CH are not prohibitively expensive for patients and healthcare insurance providers. Apart from CMS, many insurers do reimburse the cost of oxygen use for CH. Our study suggests that further research is needed to determine if a lack of physician awareness about treatments and ways to prescribe are barriers for patients to access the high‐flow oxygen treatment.